A Study Of Internet Protocol Digital Microwave Radio (IP DMR) Propagation Delay Affected Downtime In Oil And Gas Company - Samsudin, Nooraida; Ahmad, Azham (SOTVI, 2019)
Â Internet Protocol Digital Microwave Radio (IP DMR) is a significantimpact on the trunk mobile communication between platform. Thus, thegoal of downtime is a crucial problem especially in oil and gascompany. Based on the examines from the previous issues such asrelative costing based on previous hardware requirements and possibleimplementation, and upgrade that contribute to the long termcommunication flexibly on all radio in the platform system. This paperwill examine the downtime that affect the network by calculate thepropagation delay using SLA given and compare the SLA for DigitalMicrowave Radio (DMR) and Internet Protocol Digital MicrowaveRadio (IP DMR) that contribute to the process